2013
DOI: 10.1152/ajprenal.00054.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin protects against renal ischemia-reperfusion injury by inhibition of oxidative stress

Abstract: Reactive oxygen species (ROS) play a critical role in renal ischemia-reperfusion injury (IRI). Intermedin (IMD) reportedly protected against myocardial IRI via its antioxidant effects; however, its protective role in renal IRI has not been investigated. We overexpressed IMD in rat kidneys and examined how the kidneys respond to renal IRI. Eukaryotic expression plasmid encoding the rat IMD gene or control empty vector was transfected into the left kidney using an ultrasound-microbubble-mediated delivery system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 38 publications
4
55
0
1
Order By: Relevance
“…In the current study, ischemia reperfusion resulted in increased MDA level as a lipid peroxidation production and decreased SOD level. These findings confirm the renal tissue changes in the pathological points and the impaired renal function as described before .A major cellular defense against ROSs is provided by SOD and catalase, which together converts superoxide radicals first to H2O2 and then molecular oxygen and water (24). Although, the mechanism of renal IR injury has been understood for several decades, no effective therapies are introduced yet (25).…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, ischemia reperfusion resulted in increased MDA level as a lipid peroxidation production and decreased SOD level. These findings confirm the renal tissue changes in the pathological points and the impaired renal function as described before .A major cellular defense against ROSs is provided by SOD and catalase, which together converts superoxide radicals first to H2O2 and then molecular oxygen and water (24). Although, the mechanism of renal IR injury has been understood for several decades, no effective therapies are introduced yet (25).…”
Section: Discussionsupporting
confidence: 85%
“…Zou et al found that pioglitazone protected against renal ischemia-reperfusion injury by increasing the level of enzymatic activities of superoxide dismutase and enhancing antioxidant capacity [43]. Similar mechanisms were seen in the protective effects of curcumin and intermedin [44] It was reported that propofol had anti-oxidative activity [45]. Propofol scavenges H 2 O 2 and reduces the formation of lipid peroxides [46], which validates in heart protection [47,48].…”
Section: Discussionmentioning
confidence: 82%
“…3 A substantial amount of study to date has focused on the mechanism of oxidative stress and cell apoptosis in renal I/R injury, so many therapeutic method aimed at oxidative stress and apoptosis has been reported to protection renal injury. [26][27][28] Nesfatin-1, an 82-amino-acid peptide, has been reported to possess antioxidative, antiinflammation and anti-apoptotic properties. Previous study showed the neuroprotection of nesfatin-1 against SAHinduced injury in rats by inhibiting inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%